A surface temperature dipole pattern between Eurasia and North America triggered by the Barents–Kara sea-ice retreat in boreal winter. (1st November 2022) - Hou, Yurong; Cai, Wenju; Holland, David M; Cheng, Xiao; Zhang, Jiankai; Wang, Lin; Johnson, Nathaniel C; Xie, Fei; Sun, Weijun; Yao, Yao; Liang, Xi; Yang, Yun; et al.
Abstract: The Arctic has experienced dramatic climate changes, characterized by rapid surface warming and sea-ice loss over the past four decades, with broad implications for climate variability over remote regions. Some studies report that Arctic warming may simultaneously induce a widespread cooling over Eurasia and frequent cold events over North America, especially during boreal winter. In contrast, other studies suggest a seesaw pattern of extreme temperature events with cold weather over East Asia accompanied by warm weather in North America on sub-seasonal time scales. It is unclear whether a systematic linkage in surface air temperature (SAT) exists between the two continents, let alone their interaction with Arctic sea ice. Here, we reveal a dipole pattern of SAT in boreal winter featuring a cooling (warming) in the Eurasian continent accompanied by a warming (cooling) in the North American continent, which is induced by an anomalous Barents–Kara sea-ice decline (increase). The dipole operates on interannual and multidecadal time scales. We find that an anomalous sea-ice loss over the Barents–Kara Seas triggers a wavenumber one atmospheric circulation pattern over the high-latitude Northern Hemisphere, with an anomalous high-pressure center over Siberia and an anomalous low-pressure center over high-latitude North America. The circulation adjustment generates the dipole temperature pattern through thermal advection. Our finding has important implications for Northern Hemisphere climate variability, extreme weather events, and their prediction and projection.